The challenge of developing meaningful curriculum initiatives for moral education in Japan. Issue 1 (2nd January 2017) - Nishino, Mayumi
Abstract: This article outlines trends in the ongoing reform of moral education in Japan by examining how this is dealing with problems and issues which have arisen from past practice in moral education in schools. The Moral Class has been incorporated in the elementary and junior high school curriculum as 'a non-subject lesson' since 1958. In 2015 the course of study was revised to upgrade the Moral Class to an official subject in order to revamp moral education for the well-being of children and of society. The focus of this reform is described as a shift to thinking and discussion with the intention that the new subject will encourage children to think reflectively and critically. It is expected that active learning, such as discussion, collaborative work and problem-solving, will enhance children's abilities to think deeply and to act proactively. Teacher education and collaboration within the society will be key to realizing the potential of this new subject.